What Factors Affect Profitability? (Case Study on Conventional National Private Bank Listing on Indonesian Stock Exchange Period 2019-2022) - Ardaranie, Rizkanandya; Mulyani, Sri; Handayani, Retno Tri (Jurnal Akuntansi dan Perpajakan, 2024)
This research aims to determine the effect of Net Interest Margin, Operating Cost with Operating Income (OCOI), Loan to Deposit Ratio, Non-Performing Loans and Capital Adequacy Ratio on Profitability in conventional national private banking companies. The population for this research is conventional national private banking companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The sampling technique used was the Purposive Sampling technique with 19 companies and the total data processed during 4 years of observation was 76 data. This research method uses panel data regression analysis using the Eviews-10. The results of this research are that Net Interest Margin, Loan to Deposit Ratio and Capital Adequacy Ratio have no effect on Return on Assets, while Operating Costs with Operating Income and Non-Performing Loans have a negative effect on Return on Assets.